Micro, Small and Medium Enterprises Strategies to Survive the Covid-19 Pandemic Conditions in Indonesia - Aprilda Yanti (Institute of Computer Science (IOCS), 2022)
The Pandemic COVID-19 has an impact on the Indonesian economy. The decline in economic performance was not only felt by large multi-national companies, or nationally but also felt by SMEs. This study aims to examine MSME survival strategies, especially in the pandemic. The research method used is the study of literature. The researcher examines various empirical study results especially imiah journals related to the MSME strategy. Researchers then compared the results of research from various journals and take the essence of the results of the research. Based on the results of the literature study, there are four survival strategies for MSMEs namely, 1) marketing with digital marketing, 2) strengthening human resources, 3) carrying out creative innovations and 4) improving service to consumers. With these strategies, it is expected that MSMEs in Indonesia can survive and survive the crisis conditions due to the COVID-19 pandemic.